2019
DOI: 10.1111/jfs.12705
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric barrier discharge cold atmospheric plasma: Bacterial inactivation mechanism

Abstract: The mechanisms of inactivation against Gram‐negative bacteria (GNB) including Pseudomonas aeruginosa, Escherichia coli, and Vibrio parahaemolyticus, and Gram‐positive bacteria (GPB) involving Listeria monocytogenes and Staphylococcus aureus, by dielectric barrier discharge cold atmospheric plasma were elucidated. Both GNB and GPB were exposed to treatment with cold plasma produced from argon/oxygen mixture (90:10) as the working gas for different treatment times (1, 2.5, and 5 min). Survival counts were reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…It has been demonstrated that Gram-negative bacteria are more sensitive than Gram-positive bacteria to CAP, a phenomenon likely to occur due differences in the cell wall thickness [ 5 ]. In agreement with our observation, Olatunde and co-workers [ 52 ] proposed the production of UV as one of the major factors in the mode of action in Gram-negative bacterial inactivation by CAP. The authors also suggested a reduced relevance of UV transmitted by CAP in the cell envelope damage of Gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…It has been demonstrated that Gram-negative bacteria are more sensitive than Gram-positive bacteria to CAP, a phenomenon likely to occur due differences in the cell wall thickness [ 5 ]. In agreement with our observation, Olatunde and co-workers [ 52 ] proposed the production of UV as one of the major factors in the mode of action in Gram-negative bacterial inactivation by CAP. The authors also suggested a reduced relevance of UV transmitted by CAP in the cell envelope damage of Gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…The specific types of reactive species, such as oxygen atoms, ozone, metastable oxygen molecules, peroxide, superoxide, and hydroxyl radicals, created by plasma are bactericidal (Lopez et al, 2019). The potential application of plasma in inactivation is based on the fact that reactive plasma species damage the deoxyribonucleic acid (DNA) in the chromosomes (Olatunde, Benjakul, & Vongkamjan, 2019). According to Equation (3), the linear effect, second‐order effect of different levels of voltage, time, and distance, as well as the interaction effect of voltage and distance, were statistically significant on total count samples, while the interaction effect of voltage–time and time–distance on this response were not statistically significant ( p > .05).…”
Section: Resultsmentioning
confidence: 99%
“…NTTs including pulsed light, high-intensity ultrasound, ionizing radiation, oscillating magnetic fields, ultraviolet light, high hydrostatic pressure, and pulsed electric fields as well as high voltage cold plasma (HVCP) have been introduced for seafood [3]. These technologies have shown promising potential in inactivating spoilage and pathogenic microorganisms in seafood without significant changes in organoleptic properties, while maintaining the food nutritive value [4,5]. Nonetheless, some negative changes toward quality, particularly protein alteration, occur depending on the type and condition of the non-thermal technology used.…”
Section: Introductionmentioning
confidence: 99%